Investigation of Structural Breaks in Markets of a Group of Arabic Countries Facing Political and Economic Instability (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The purpose of this study is to investigate the structural breaks in the financial markets of a group of Arab countries facing political and economic instability (Syria, Lebanon, Egypt, Bahrain, Tunisia) and determine the timing and significance of these structural breaks during the period (2010-2021). The study has applied the traditional unit root test (ADF) in addition to the modern unit root test that take into account the structural breaks in the time series Zivot and Andrews (1992) test and Lee and Strazicich (2003) test.The results showed that the traditional unit root tests has failed in determining the stationary level of the time series variables accurately because it doesn’t take into account the existence of structural breaks. The results show that the political and economic instability in markets under study caused a significant structural breaks in the financial markets of these countries, and also the COVID 19 has a limited effect on the financial markets of countries under study.